2020
DOI: 10.1002/rth2.12332
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of thrombin generation 12 hours after intake of direct oral anticoagulants

Abstract: Background The residual antithrombotic activity 12 hours after intake of direct oral anticoagulants (DOACs) is of clinical relevance in the setting of bleeding or urgent surgery. Objective To evaluate the effects of DOACs on thrombin generation 12 hours after DOAC intake in comparison to baseline and a healthy control group. Methods Eighty patients were recruited, 20 patients for each approved DOAC: apixaban, edoxaban, rivaroxaban, and dabigatran. The patients were either to be put on anticoagulation for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In order to compare in vitro the effect of rivaroxaban and apixaban on TG parameters, we chose to use frozen normal plasma (Cryocheck) spiked with increasing concentrations of xabans. Increasing xabans concentrations prolonged TG temporal parameters and decreased values of PH and ETP in a concentration‐dependant manner as previously shown in vitro as well as ex vivo 17,19‐21,26‐28 . These data confirm that measurement of TG parameters with ST Genesia enabled a reliable assessment of the PD response to rivaroxaban and apixaban, PH being more reliable than ETP 19‐21 .…”
Section: Discussionsupporting
confidence: 86%
“…In order to compare in vitro the effect of rivaroxaban and apixaban on TG parameters, we chose to use frozen normal plasma (Cryocheck) spiked with increasing concentrations of xabans. Increasing xabans concentrations prolonged TG temporal parameters and decreased values of PH and ETP in a concentration‐dependant manner as previously shown in vitro as well as ex vivo 17,19‐21,26‐28 . These data confirm that measurement of TG parameters with ST Genesia enabled a reliable assessment of the PD response to rivaroxaban and apixaban, PH being more reliable than ETP 19‐21 .…”
Section: Discussionsupporting
confidence: 86%
“…Preliminary observations showed that thrombin generation testing is affected by all anticoagulant drugs, suggesting that this assay could be useful in assessing DOAC activity, but this deserves further confirmation in larger cohorts to validate this approach since to date, the role of TGA for clinical decision-making in DOAC-treated patients is not clear. 68,[70][71][72]…”
Section: Doac and Thrombin Generation Assaysmentioning
confidence: 99%
“…2). 24,[66][67][68][69][70][71] The ST Genesia (Diagnostica Stago, Asnières sur Seine Cedex, France), an automated analyzer for thrombin generation testing has the potential for a wide implementation in routine laboratories. Preliminary observations showed that thrombin generation testing is affected by all anticoagulant drugs, suggesting that this assay could be useful in assessing DOAC activity, but this deserves further confirmation in larger cohorts to validate this approach since to date, the role of TGA for clinical decision-making in DOAC-treated patients is not clear.…”
Section: Doac and Thrombin Generation Assaysmentioning
confidence: 99%
“…TGA has been applied in drug development to explore pharmacological principles and drug related side effects. TGA has for example been recently evaluated in dose finding studies of direct oral anticoagulants and to tailor therapeutic protocols with such substances 45‐48 …”
Section: Applications In Basic Science Non‐clinical Research and Quality Control Of Pharmaceuticalsmentioning
confidence: 99%